2015
DOI: 10.1590/0102-311x00136014
|View full text |Cite
|
Sign up to set email alerts
|

The “Healthy Habits, Healthy Girls” randomized controlled trial for girls: study design, protocol, and baseline results

Abstract: The purpose of this article is to describe the study design, protocol, and baseline results of the “Healthy Habits, Healthy Girls” program. The intervention is being evaluated through a randomized controlled trial in 10 public schools in the city of São Paulo, Brazil. Data on the following variables were collected and assessed at baseline and will be reevaluated at 7 and 12 months: body mass index, waist circumference, dietary intake, nutrition, physical activity, social cognitive mediators, physical activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 43 publications
0
49
0
7
Order By: Relevance
“…Deste total, alguns estudos eram referentes aos mesmos programas de intervenção. Sendo assim, foram agrupados e analisados de forma conjunta, com o objetivo de complementar as informações das respectivas intervenções: "Saúde na Boa" 4,19-23 , "Hábitos Saudáveis, Meninas Saudáveis" 24,25 , e "Fortaleça sua saúde" 5,26 totalizando sete programas de intervenção para AF.…”
Section: Resultados Seleção Dos Artigosunclassified
See 3 more Smart Citations
“…Deste total, alguns estudos eram referentes aos mesmos programas de intervenção. Sendo assim, foram agrupados e analisados de forma conjunta, com o objetivo de complementar as informações das respectivas intervenções: "Saúde na Boa" 4,19-23 , "Hábitos Saudáveis, Meninas Saudáveis" 24,25 , e "Fortaleça sua saúde" 5,26 totalizando sete programas de intervenção para AF.…”
Section: Resultados Seleção Dos Artigosunclassified
“…Quanto ao ano, os estudos aconteceram no período de 2006 a 2015, cuja maioria foi realizada nas regiões Sul 27,28 e Sudeste do país 24,25,29,30 . Foi encontrado apenas um programa de intervenção na região nordeste 5,26 .…”
Section: Descrição Dos Programas De Intervençãounclassified
See 2 more Smart Citations
“…The study design, protocol and baseline results are reported in detail elsewhere (Leme and Philippi, 2015). In summary, it was a six-month school-based group randomized controlled trial named "Healthy Habits, Healthy Girls -Brazil (H3G --Brazil)".…”
Section: Study Design and Participantsmentioning
confidence: 99%